2018
DOI: 10.1101/247965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in Genome-wide NF-kappaB RELA Binding Sites upon Microbial Stimuli and Identification of a Virus Response Profile

Abstract: NF-kB transcription factors are master regulators of the innate immune response. Activated downstream of pathogen recognition receptors, they regulate the expression of genes to help fighting infections as well as recruiting the adaptive immune system. NF-kB responds to a wide variety of signals, but the processes by which stimulus-specificity is attained remain unclear. Here, we characterized the response of one NF-kB member, RELA, to four stimuli mimicking infection in human nasopharyngeal epithelial cells. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…A single macrophage is estimated to harbor around 2.5 × 10 5 NF‐κB p65 molecules . On the other hand, ChIP‐seq studies in human cell lines have identified between 10,000 and 70,000 immediately accessible p65 binding sites per haploid set of chromosomes . For instance, Detroit 562 cells analyzed after a 80 min LPS stimulation demonstrate 12,198 p65 binding sites; 14,069 sites are detected in THP‐1 cells after a 60 min TNF stimulation .…”
Section: Mechanisms Of Nod‐tlr Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single macrophage is estimated to harbor around 2.5 × 10 5 NF‐κB p65 molecules . On the other hand, ChIP‐seq studies in human cell lines have identified between 10,000 and 70,000 immediately accessible p65 binding sites per haploid set of chromosomes . For instance, Detroit 562 cells analyzed after a 80 min LPS stimulation demonstrate 12,198 p65 binding sites; 14,069 sites are detected in THP‐1 cells after a 60 min TNF stimulation .…”
Section: Mechanisms Of Nod‐tlr Interactionsmentioning
confidence: 99%
“…On the other hand, ChIP‐seq studies in human cell lines have identified between 10,000 and 70,000 immediately accessible p65 binding sites per haploid set of chromosomes . For instance, Detroit 562 cells analyzed after a 80 min LPS stimulation demonstrate 12,198 p65 binding sites; 14,069 sites are detected in THP‐1 cells after a 60 min TNF stimulation . Although these estimates are very rough, they indicate that if IκB has been totally degraded, then even a minor part of the available NF‐κB p65 pool is sufficient to saturate accessible NF‐κB p65 binding sites in the genome.…”
Section: Mechanisms Of Nod‐tlr Interactionsmentioning
confidence: 99%